New species, synonymy, and new record in Neotropical Acanthocinini (Coleoptera, Cerambycidae, Lamiinae) - Monné, Miguel A.; Santos-Silva, Antonio (Zootaxa, 2022)
Three new species and one new genus of Bolivian Acanthocinini are described: Lepturges (Lepturges) auratus sp. nov.; Leptostylus dentatus sp. nov.; and Spiritusellus personatus, gen. nov. et sp. nov. Notes on the differences between Leptostylus batesi Casey, 1913, and L. hilaris Bates, 1872 are provided in the remarks of L. dentatus sp. nov. A new country record (Bolivia) is reported for Nealcidion latipenne (Bates, 1863) and Nyssodrysternum lanceolatum Monné & Tavakilian, 2011 is synonymized with Atrypanius infimus (Bates, 1885).